Manajemen Program Majoring dalam Mengembangkan Minat dan Bakat Siswa di Sekolah National Plus Carnegie Medan - Nadya Prastieca Nasution (Departement of Mathematics Education, 2024)
This study examines the management of majoring activities to enhance students' interests and talents at Carnegie School Medan. The conclusions drawn from the research and discussion are as follows: Planning for majoring activities is conducted at the beginning of each academic year by the school principal, majoring activity coordinators, and majoring teachers. Majoring activities are mandatory for all students from grade 4 to grade XII, three times a week from Monday to Wednesday. The implementation of majoring activities runs smoothly, involving students and teachers in experiments, actions, and direct product creation. Evaluation is conducted monthly with supervision 2-3 times per month using the Alkin method by the QC team. Evaluation covers the implementation of lesson plans, student involvement, and learning outcomes. Feedback from evaluations is used to improve subsequent majoring activities. This program demonstrates clear planning and efficient implementation in enhancing students' interests and talents.